Development of Website-Based Learning Media in Grammatics Course A1 - Indah Surya Cerah Marpaung; Pujiastuti, Suci (Asian Journal of Applied Education (AJAE), 2024)
The purpose of this study is to find out the difficulties faced by class C 2023 students of the German Language Study Program, State University of Medan, in learning Germany using web-based learning media for the A1 Grammar course. This paper is a literature study that uses a quantitative descriptive method with the theory of Richey and Klein 2009. The data of this research is in the form of material taken from the book "Textbook for Learning Germany Grammar" by Ahmad Sahat Pardamean, Tanti Kurnia Sari and Siti Kudriyah (2018), the Germany grammar exercise book by Dreyer and Schmitt (2019) and the Grundstufen-Grammatic book by Monika Reimann (2010). This research was conducted in the language laboratory of the Department of Foreign Languages, State University of Medan. The results of the study show that web-based learning media for Grammatics A1 courses with preposition topics with accusation can be used by teachers and students when learning Germany.